What are the risk factors for postoperative infections of third molar extraction surgery: A retrospective clinical study-? - Sukegawa, Shintaro (Med Oral Patol Oral Cir Bucal, 2019)
BACKGROUND: This study aimed to identify (1) the predilection site of postoperative infection after third molar extraction surgery, (2) risk factors associated with postoperative infection, and (3) the cause of the difference between delayed- and early-onset infections. MATERIAL AND METHODS: This retrospective study included 1010 patients (396 male, 614 female) who had ≥1 third molars extracted (2407; 812 maxilla, 1595 mandible). The risk factors were classified as attributes, general health, anatomic, and operative. Outcome variables were delayed- and early-onset infections. RESULTS: Postoperative infection was completely absent in the maxilla, and all infections occurred in the mandible, with a probability of 1.94% (31/1595). Bivariate analysis for postoperative infection showed depth of inclusion and intraoperative hemostatic treatment to be significantly associated with the development of infections. Bivariate analysis for delayed- and early-onset infections showed simultaneous extraction of the left and right mandibular third molars to be prominent risk factors. CONCLUSIONS: Postoperative infection occurs mainly in the mandible, and that in the maxilla is very rare. The risk of postoperative infection in the mandible was found to be related to the depth of inclusion and intraoperative hemostatic treatment. Simultaneous extraction of the left and right mandibular third molars appear to increase the risk of delayed-onset postoperative infection. Key words:Third molar extraction surgery, delayed-onset infection, early-onset infection, postoperative infection.